Autonomic balance and cardiovascular hemodynamic function in men with prolactinoma - Włochacz, Agnieszka; Krzesiński, Paweł; Wierzbowski, Robert; Uziębło-Życzkowska, Beata; Witek, Przemysław; Zieliński, Grzegorz; Kazimierczak, Anna; Banak, Małgorzata; Włochacz, Bartłomiej; Gielerak, Grzegorz (Frontiers in Endocrinology, 2025)
IntroductionEndocrine disorders associated with prolactinoma (PR) in men may affect the interaction between the cardiovascular and autonomic nervous system (ANS). The aim of this study was to evaluate the association of sympathetic-parasympathetic balance, assessed by heart rate variability (HRV) analysis, with cardiovascular hemodynamic function, assessed by impedance cardiography (ICG) and applanation tonometry (AT), in men with newly diagnosed PR.MethodsIn this observational cohort study, 20 men with newly diagnosed PR and no significant comorbidities were included. A correlation analysis was performed on parameters assessed by ICG and AT with HRV indices assessed by 24-hour Holter ECG recordings. The ICG assessment included indicators of heart’s pumping efficiency: the acceleration index (ACI), the velocity index (VI), and the Heather index (HI). The AT assessment included aortic augmentation pressure (AP) and augmentation index (AI). Heart rate variability analysis incorporated time-domain parameters (pNN50, SDNN, SDSD, RMSSD) and frequency-domain parameters (total power (TP) and its individual frequency bands: low frequency (LF day/night) and high frequency (HF day/night), LF/HF day/night ratio). Furthermore, echocardiographic assessment was performed.ResultsMen with PR demonstrated significant correlations between cardioimpedance parameters of heart’s pumping efficiency (ACI, HI, VI) with selected time- and frequency-domain parameters of HRV. Furthermore, significant correlations of central pressure values with selected time-and frequency-domain HRV parameters were found: a) higher AP corresponded with lower values of pNN50_day (R=-0.53, p=0.019), RMSSD_night (R=-0.49, p=0.033), pNN50_night (R=-0.49, p=0.034), TP_day (R=-0.53; p=0.02) and TP_ night (R=-0.67; p=0.002); b) higher AI corresponded with lower values of RMSSD_day (R=-0.46; p=0.047), SDSD_day (R=-0.47; p=0.044), pNN50_day (R=-0.53; p=0.021), RMSSD_night (R=-0.54; p=0.016), SDSD_night (R=-0.52; p=0.021), pNN50_night (R=-0.51; p=0.027), TP_day (R=-0.57; p=0.011) and TP_night (R=-0.69; p=0.002).ConclusionsIn men with newly diagnosed PR, the association of poorer heart’s pumping efficiency and elevated indirect indicators of arterial stiffness with a shift away from parasympathetic influence was confirmed.